2014
DOI: 10.5897/jdae2013.006
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and adoption of improved cassava varieties and processing technologies in Nigeria

Abstract: Development of high yielding and disease resistant cassava varieties, coupled with the promotion of efficient processing technologies, was the principal intervention aimed at changing the cassava subsector in Nigeria. National research and extension programs in Nigeria and IITA have been spearheading efforts to disseminate these varieties alongside improving farmer's access to processing machineries. Several Research-for-Development (R4D) projects were implemented to this effect between early 1980 to date. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 13 publications
7
49
0
1
Order By: Relevance
“…There is a positive relationship between awareness and adoption of improved pearl millet production practices. This agrees with the findings of Abdoulaye et al, (2014) which reported a positive relationship between awareness and adoption of improved cotton production practices in Katsina State. Table 3 reveals that 42.2% of the adopters and 21.0% of the nonadopters of improved pearl millet practices posited that inaccessibility to improved seeds was one of the major constraints to the adoption of the practices in the study area.…”
Section: Determinants Of Adoption Of Improved Pearl Millet Productionsupporting
confidence: 92%
“…There is a positive relationship between awareness and adoption of improved pearl millet production practices. This agrees with the findings of Abdoulaye et al, (2014) which reported a positive relationship between awareness and adoption of improved cotton production practices in Katsina State. Table 3 reveals that 42.2% of the adopters and 21.0% of the nonadopters of improved pearl millet practices posited that inaccessibility to improved seeds was one of the major constraints to the adoption of the practices in the study area.…”
Section: Determinants Of Adoption Of Improved Pearl Millet Productionsupporting
confidence: 92%
“…In a recent study conducted by Abdoulaye et al (2014) ICVs adopters were observed to have a higher yield of about 16 tons/ha compared with 10 tons/ha for nonadopters. The implication is that the desired increase in productivity due to the ICVs and the subsequent impact on poverty reduction will not be achieved unless the ICVs are widely adopted by the Nigerian farmers.…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to the fact that farmers were interested in income generating farm enterprises in order to meet household financial obligations. Similar studies have shown positive effect of income both on and off-farm on technology adoption [35,36]. Therefore, any efforts to enhance household income either from farm and offfarm activities including credit would enhance technology adoption like TCB.…”
Section: Banana Incomementioning
confidence: 85%